1984
DOI: 10.1002/1097-0142(19840715)54:2<235::aid-cncr2820540210>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy alone in the treatment of carcinoma of the uterine cervix. II. Analysis of complications

Abstract: A retrospective analysis was carried out on 811 patients with histologically proven invasive carcinoma of the uterine cervix treated with irradiation alone. A correlation was made of the doses of irradiation delivered to the pelvic organs with external beam and intracavitary insertions. Approximately 3% of the patients exhibited grade 2 gastrointestinal complications, and 2% developed grade 2 urinary complications; 5% of the patients developed grade 3 gastrointestinal complications, and 3% developed grade 3 ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
92
1
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(97 citation statements)
references
References 15 publications
2
92
1
2
Order By: Relevance
“…8,25,30 In a few studies however, late complications occurring after Ͼ 10 years of treatment have been observed. In the current series, rectosigmoid colon complications occurred most frequently during the first 2 years, after which the incidence decreased markedly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,25,30 In a few studies however, late complications occurring after Ͼ 10 years of treatment have been observed. In the current series, rectosigmoid colon complications occurred most frequently during the first 2 years, after which the incidence decreased markedly.…”
Section: Discussionmentioning
confidence: 99%
“…In their LDR series, Perez et al 30 and Pourquier et al 31 demonstrated a positive correlation between a dose to the rectum and bladder of Ͼ 80 Gy and severe complications. They reported that the rates of Grade 2 and 3 complications in the urinary tract and rectosigmoid colon were approximately 5% with doses Ͻ 75-80 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,25,26 In contrast to conventional treatments, IMRT significantly spares the OAR (Table 2). In our series, the small bowel median V40 and V45 of 77 cc and 7 cc, respectively, could not be obtained using conventional 3D conformal therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Because most centers treat patients who have uterine cervical carcinoma with the Point A dose, many previous studies [5][6][7][8] did not analyze the influence of the BED Point A on the risk of LRC. In addition, some investigators 9,28 noted that the EBRT dose and BED Point A did not correlate with LRC. In the current study, although the EBRT dose and BED Point A were correlated with LRC Ն Grade 2 in the univariate analysis, those parameters were not correlated in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] previously demonstrated that various clinical and treatment-related parameters, including age, diabetes mellitus, disease stage, EBRT dose, fractionation of brachytherapy, Point A dose, and rectal dose, were correlated with late rectal complications (LRC). In particular, RT dose and volume are considered the most important parameters associated with LRC.…”
mentioning
confidence: 99%